Pengembangan Media Pembelajaran Berbasis Web Pada Mata Pelajaran Dasar Teknik Jaringan Komputer dan Telekomunikasi - Nadia Putri; Haris Kurniawan; Rahayu Trisetyowati Untari (Unversitas Muhammadiyah Mataram, 2024)
Abstract: The aim of this research is to produce web-based learning media on the basic subjects of computer network engineering and telecommunications at SMK Negeri 1 Ampek Angkek that are valid and practical. The type of research used in this research is Research and Development (R&D) with the ADDIE development model which consists of several stages, namely, Analysis, Design, Development, Implementation, and Evaluation. The subjects used in this research were 37 students in class X TKJ. Meanwhile, the instruments in this research used questionnaire validation sheets by media experts and material experts as well as practicality questionnaires by teachers and students.The results of the research show that the results of the expert validity of web-based learning media obtained a score of 83.10% in the very valid category, while for the validity of the material expert the score was 89.06% in the very valid category. Meanwhile, for the practicality level, teachers got a score of 90.10% in the very practical category and for the practicality level, students got a score of 83,25% in the very practical category. Based on this data, it can be concluded that web-based learning media is suitable for use in the learning process.Abstrak: Tujuan dari penelitian ini adalah untuk mengehasilkan media pembelajaran berbasis web pada mata pelajaran dasar teknik jaringan komputer dan telekomunikasi di SMK Negeri 1 Ampek Angkek yang valid dan praktis. Jenis penelitian yang digunakan dalam penelitian ini adalah Research and Development (R&D) dengan model pengembangan ADDIE yang terdiri dari beberapa tahap yaitu, Analysi, Design, Development, Implementation, and Evaluation. Sebjek yang digunakan dalam penelitian ini yaitu siswa kelas X TKJ yang berjumlah 37 siswa. Sementara instrumen pada penelitian ini menggunakan lembar validasi angket oleh ahli media dan ahli materi serta angket praktikalitas oleh guru dan siswa. Hasil penelitian menunjukkan bahwa hasil dari validitas ahli media pembelajaran berbasis web memperoleh nilai sebesar 83,10% dengan kategori sangat valid sedangkan untuk validitas ahli materi memperoleh nilai sebesar 89,06% dengan kategori sangat valid. Sementara untuk tingkat praktikalitas guru memperoleh nilai sebesar 90,10% dengan kategori sangat praktis dan untuk tingkat praktikalitas siswa memperoleh nilai sebesar 83,25% dengan kategori sangat praktis.